PENGARUH PENERAPAN PEMBELAJARAN DARING TERHADAP KUALITAS LAYANAN AKADEMIK PADA MASA PANDEMI COVID-19 DI SMK TI BALI GLOBAL - Ni Luh Putri Srinadi; Anggun Nugroho; Putu Riska Yunita Srinandari (Prosiding, 2022)
During the CoViD-19 pandemic, online learning has a significant role in student learning in secondary schools, especially vocational schools. In this study, we want to know the influence and relationship between online learning and academic quality service. To improve the quality of service and the learning process, this research was conducted at SMK TI Bali Global which consists of several classes. Based on preliminary research in several schools in Bali, almost all learning processes have been supported by adequate laboratory facilities and technology for schools such as LCD projectors, screens and blackboards in each class as well as internet network access. Overall, this study aims to strengthen the belief that online learning is an element that influences academic quality service during the CoViD-19 pandemic. A questionnaire was applied to collect data from students at SMK TI Bali Global. Furthermore, to perform data analysis, statistical methods will be used